DEFINIÇÃO DE ESCALAS DE EFICIÊNCIA ENERGÉTICA DA ENVOLTÓRIA EM EDIFICAÇÕES RESIDENCIAIS: ETIQUETAGEM BRASILEIRA - Olinger, Marcelo Salles; Mazzaferro, Leonardo; Machado, Rayner Maurício e Silva; Eli, Letícia Gabriela; Melo, Ana Paula; Fossati, Michele; Lamberts, Roberto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The aim of this study is to define the energy efficiency classification for the Brazilian Regulation for residential buildings. a reference case, based on the minimum standards defined by NBR 15575. A database of 1 million cases was defined to fully explore the potential of different building characteristics. The results from cooling and heating thermal loads for each case were obtained from the simplified method of the new regulation, based on a metamodel developed through artificial neural networks. The energy efficiency classification was determined based on the relative differences of the thermal loads between all cases and their reference cases. The relative difference results for each label were specified for different climates, zone areas and use patterns.